Clinical use of orthodontic mini-implants for intrusion and retraction: a systematic review - Oswal Sanjam; Agarkar Sanket S.; Jethe Sandeep; Yerawadekar Sujata; Kawale Pradeep; Deshmukh Sonali; Rahalkar Jayesh S. (Sciendo, 2020)
Bimaxillary dental protrusion is common in many ethnic groups and is generally treated by the extraction of all first premolars. However, temporary anchorage devices (TADs) are currently gaining popularity and most studies have focused on anchorage loss, treatment duration, mini-implant success and failure rates, pain, discomfort and root resorption. Few studies have focused on the clinical effectiveness of implants for the intrusion and retraction of anterior teeth.